Microstructural and chemical study on an expansive dolostone from Argentina - Milanesi, Carlos Alberto (2016)
An Argentinian fine-grained dolostone has proved to react deleteriously with alkalis following a mechanism similar to ACR. As this reaction is very controversial, the rock was reassessed for going deeper into the knowledge of its reactivity. The effect of the aggregate grain size on mortar expansion was evaluated by comparing RILEM AAR-2´s test results with those from Lu et al. test method. The inhibiting effect of a high-level replacement of low-calcium fly ash was also tested. The influence of rock porosity was studied on rock and concrete prisms, stored under conditions similar to ASTM C586 and RILEM AAR-3, respectively. Microstructural and chemical studies (mercury porosimetry, polarizing microscopy, XRD, SEM-EDS) were carried out on fresh and tested rock samples. The amount of alkali-silica gel observed was very low to explain mortar or concrete expansion. Fly ash failed to inhibit mortar expansion. The only correlation observed was between concrete expansion and degree of dedolomitization.